Reinterpreting the authority of heads: Making space for values-led school improvement with the Index for Inclusion. (January 2018) - Higham, Rupert; Booth, Tony
To what extent can heads use an inclusive values-led approach to school development in the face of pressures from Ofsted and their Local Authority to focus almost exclusively on attainment outcomes? We explore leadership of school improvement in a qualitative study of 10 head teachers in the English county of 'Preshire', who worked with the third edition of the Index for Inclusion, (Booth and Ainscow 2011), a guide to values-led school improvement. We situate the study within a review of conflicting research advice about the characteristics of successful heads and how 'values', seen as motives for action, affect the recommendations from research. We found that the heads were able to use shared inclusive values to accomplish, with their staff, a degree of control over the way their schools are improved. To an extent they were able to resist extreme local pressures to engage in short term strategies to force up attainments. By making their inclusive values explicit they showed courage rather than compliance. To varying degrees they used 'the Index' to create inclusive, democratic and sustainable school improvement plans while conforming to Ofsted requirements. We consider the possibilities for more widespread implementation of school development led by inclusive values.